2004
DOI: 10.1071/ea02123
|View full text |Cite
|
Sign up to set email alerts
|

Water use efficiency and profitability on an irrigated dairy farm innorthern Victoria: a case study

Abstract: A study was conducted to look at water use efficiency and profitability on an irrigated dairy farm in northern Victoria. For this case study farm, an economic evaluation was performed for various development options that could result in higher water use efficiency, increased profit, and meet the farm owners' objectives. Water use efficiency was defined as the amount of milk (kg milk fat plus protein) produced from pasture per megalitre of water (irrigation plus effective rainfall).The case study farm data indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 8 publications
2
13
0
1
Order By: Relevance
“…This agrees with previous research in Morocco (Sraïri et al, 2009a) and other countries (Armstrong, 2004;Sultana et al, 2014). High variability among farms was observed, reflecting differences resulting from on-farm practices in all production functions, from water to cattle products.…”
Section: Discussionsupporting
confidence: 92%
“…This agrees with previous research in Morocco (Sraïri et al, 2009a) and other countries (Armstrong, 2004;Sultana et al, 2014). High variability among farms was observed, reflecting differences resulting from on-farm practices in all production functions, from water to cattle products.…”
Section: Discussionsupporting
confidence: 92%
“…Depending on their strategic goals and practices, dairy farmers required between 1.2 and 1.8 m 3 of water to produce 1 kg of milk (Sraïri et al, 2008). These values are close to the findings of Armstrong (2004) in Australian semi-arid conditions (1.0 m 3 of water per kg of milk). Such results imply that dairy cattle systems should pay extra attention to preserving this vital resource by selecting appropriate forage species according to each region's climatic and hydraulic characteristics (Gilibert, 1992).…”
Section: Introductionsupporting
confidence: 65%
“…This suggested that there was scope for many farms to increase efficiency and productivity by modifying farm management practices depending on the input variables. However, later studies found no relationship between a reduction in irrigation water allocations and an increase in WUE [21] and no simple, direct association between WUE and profitability [22].…”
Section: Introductionmentioning
confidence: 92%
“…This suggested that there was scope for many farms to increase efficiency and productivity by modifying farm management practices depending on the input variables. However, later studies found no relationship between a reduction in irrigation water allocations and an increase in WUE [21] and no simple, direct association between WUE and profitability [22]. A survey of irrigated dairy farms in the region conducted about 20 years ago [20] found that there was a large range of water use efficiencies (WUE) ( Table 1) between farms (25-115 kg milk fat plus protein/ML water).…”
Section: Introductionmentioning
confidence: 99%